The Kingfisher Illustrated Nature Encyclopedia - Burnie, David; Edited by Smith, Miranda ; Mclean, Russell ; and Borton, Paula (London Kingfisher Publication, 2004)
This companion volume to "The Kingfisher Illustrated Animal Encyclopaedia" is a guide to the living world and its inhabitants - both flora and fauna. This reference explores plant and animal groups, illustrating the range of living things that is found in every corner of the planet.
Include Color Illustration, Glossary, Websites and Index
Keywords: Natural history -- Nature